Teknologi Mandiri Benih Padi Berbasis Masyarakat Mendukung Pengembangan Tanaman Padi Terpadu ci Bali - I Gusti Komang Dana Arsana; Ida Bagus Kade Suastika (Universitas Muhammadiyah Purworejo, 2018)
The government through the Directorate General of Food Crops has carried out a movement of technology transfer through the Integrated Plant Management Field School (SL-PTT) program from year to year since 2008, the area has continued to increase, in the application of superior varieties produced quite a lot, often the seeds are not yet available. The purpose of the assessment is to produce seed sources so that they are available to support rice farming. Activities in rice fields owned by farmers with farmer groups in Subak Guama Tabanan, January - April 2017. 30 hectares in an area of ​​180 hectares. The rice varieties used were Inpari 30 Ciherang Sub-1, Inpari 40 rainfed, Cigeulis, Ciherang. The data from the observations were analyzed for variance (analysis of variance) to determine the significance of the effect of water treatment and varieties as well as interactions using the F test at the 5% and 1% levels. If there is a significant effect of the treatment for a certain character, then the comparison of the mean pairs of these characters is tested based on Duncan's Multiple Distance levels of 5% and 1%. The results showed that the percentage of filled grain/panicle Inpari 40 was not significantly different from the Cigeulis and Ciherang varieties, namely 135.8 grains compared to 137.2 and 144.6 grains, while the number of filled grains/panicles of Inpari 30 Ciherang sub-1 was significantly different. with Inpari 40 rainfed VUB, Cigeulis and Ciherang namely 51.74% compared to 73.21%, 168.45%, and (82.69%). Meanwhile, the weight of 1000 grain of rainfed Inpari 40 variety was significantly different from Cigeulis but smaller and different from Ciherang, namely 28.2 g compared to 27.6 g and 30.3 g. The conclusion is that the yield of harvested dry unhulled rice as a candidate for seed shows that there is no significant difference between the varieties with an average of 6 tons per ha.Key words: Independent, Seed, Rice, and Community